The state of translation of Kazakh literature into Chinese and Translation of Abai’s works into Chinese - Saishanhuli, W. (Journal of Oriental Studies, 2023)
Translation of literary works enriches the language and helps to connect dissimilar ideas. Readers get acquainted with other foreign cultures through literary works of different countries and ethnic groups, and by reading translations of literary works of different countries, they promote mutual understanding and sharing of different values ​​between different groups in society. Literary translation plays an important role in the promotion of cultural exchanges between countries and people-to-people contacts, in making people aware of common and universal problems and special experiences of some people. In this article, we will focus on the state of translation of Kazakh literature into Chinese. The translation of Kazakh literature into Chinese before the Great Cultural Revolution, after the Great Cultural Revolution, and the translation of the literature of independent Kazakhstan is divided into eras, briefly sorted and collected. We will also think about the translation of Abai’s works and scientific research about Abai.